Effect of trehalose on heart functions in rats model after myocardial infarction: assessment of novel intraventricular pressure and heart rate variability - Farag, Ahmed; Mandour, Ahmed S.; Kaneda, Masahiro; Elfadadny, Ahmed; Elhaieg, Asmaa; Shimada, Kazumi; Tanaka, Ryou (Frontiers in Cardiovascular Medicine, 2023)
ABSTRACT Background: Myocardial infarctions remain a leading cause of global deaths. Developing novel drugs to target cardiac remodeling after myocardial injury is challenging. There is an increasing interest in exploring natural cardioprotective agents and non-invasive tools like intraventricular pressure gradients (IVPG) and heart rate variability (HRV) analysis in myocardial infarctions. Trehalose (TRE), a natural disaccharide, shows promise in treating atherosclerosis, myocardial infarction, and neurodegenerative disorders. Objectives: The objective of this study was to investigate the effectiveness of TRE in improving cardiac functions measured by IVPG and HRV and reducing myocardial remodeling following myocardial infarction in rat model. Methods: Rats were divided into three groups: sham, myocardial infarction (MI), and trehalose-treated MI (TRE) groups. The animals in the MI and TRE groups underwent permanent ligation of the left anterior descending artery. The TRE group received 2% trehalose in their drinking water for four weeks after the surgery. At the end of the experiment, heart function was assessed using conventional echocardiography, novel color M-mode echocardiography for IVPG evaluation, and HRV analysis. After euthanasia, gross image scoring, histopathology, immunohistochemistry, and quantitative real-time PCR were performed to evaluate inflammatory reactions, oxidative stress, and apoptosis. Results: The MI group exhibited significantly lower values in multiple IVPG parameters. In contrast, TRE administration showed an ameliorative effect on IVPG changes, with results comparable to the sham group. Additionally, TRE improved HRV parameters, mitigated morphological changes induced by myocardial infarction, reduced histological alterations in wall mass, and suppressed inflammatory reactions within the infarcted heart tissues. Furthermore, TRE demonstrated antioxidant, anti-apoptotic and anti-fibrotic properties Conclusion: The investigation into the effect of trehalose on a myocardial infarction rat model has yielded promising outcomes, as evidenced by improvements observed through conventional echocardiography, histological analysis, and immunohistochemical analysis. While minor trends were noticed in IVPG and HRV measurements. However, our findings offer valuable insights and demonstrate a correlation between IVPG, HRV, and other traditional markers of echo assessment in the myocardial infarction versus sham groups. This alignment suggests the potential of IVPG and HRV as additional indicators for future research in this field.